ANALISIS SUKU BUNGA, PAJAK, DAN INVESTASI TERHADAP PENYALURAN KREDIT DOMESTIK PADA NEGARA ASEAN 5 - Aprilia, Yuyun Fahira; Silvi Asna Prestianawati (Contemporary Studies in Economic, Finance and Banking, 2024)
The purpose of this research is to analyse the effect of interest rates, taxes, and investment on domestic credit distribution lendin in ASEAN 5 countries. This research is classified as descriptive quantitative using secondary data from the World Bank website from 2013 to 2022 by taking a sample of ASEAN 5 countries namely Indonesia, Singapore, Malaysia, the Philippines, and Thailand. The analysis used is panel data regression. This research is expected to contribute positively to government policy in an effort to improve credit quality in Indonesia, Singapore, Malaysia, the Philippines, and Thailand. The results of this research show that interest rates and the number of new businesses registered have a significant positive result on domestic credit distribution in ASEAN 5 countries, meaning that the higher the interest rate and the number of new businesses registered will cause domestic credit distribution in ASEAN 5 countries to also increase. increase. Meanwhile, taxes show a significant negative result on domestic credit distribution in ASEAN 5 countries, meaning that lower taxes cause domestic credit distribution in ASEAN 5 countries to increase.